Speed of sound data and acoustic virial coefficients of two binary (N2 + H2) mixtures at temperatures between (260 and 350) K and at pressures between (0.5 and 20) MPa. (August 2022) - Segovia, José J.; Lozano-Martin, Daniel; Tuma, Dirk; Moreau, Alejandro; Carmen Martín, M.; Vega-Maza, David
Highlights: New experimental speed of sound data and acoustic virial coefficients of (N2 + H2 ) mixtures. The performance of three established reference thermodynamic models is assessed. Beckmüller et al. EoS (10.1063/5.0040533) performs best within the studied ranges. Abstract: This work aims to address the technical concerns related to the thermodynamic characterization of gas mixtures blended with hydrogen for the implementation of hydrogen as a new energy vector. For this purpose, new experimental speed of sound measurements have been done in gaseous and supercritical phases of two binary mixtures of nitrogen and hydrogen using the most accurate technique available, i.e., the spherical acoustic resonator, yielding an experimental expanded ( k  = 2) uncertainty of only 220 parts in 10 6 (0.022%). The measurements cover the pressure range between (0.5 and 20) MPa, the temperature range between (260 and 350) K, and the composition range with a nominal mole percentage of hydrogen of (5 and 10) mol%, respectively. From the speed of sound data sets, thermophysical properties that are relevant for the characterization of the mixture, namely the second β a and third γ a acoustic virial coefficients, are derived. These results are thoroughly compared and discussed with the established reference mixture models valid for mixtures of nitrogen and hydrogen, such as the AGA8-DC92 EoS, the GERG-2008 EoS, and the recently developed adaptation of the GERG-2008 EoS, here denoted GERG- H2 _improved EoS. Special attention has been given to the effect of hydrogen concentration on those properties, showing that only the GERG- H2 _improved EoS is consistent with the data sets within the experimental uncertainty in most measuring conditions.